(untitled) (Bangladesh Journal of Neuroscience, 2026)
Hallervorden-Spatz disease is a rare neurometabolic disorder characterized by iron accumulation in the brain, manifesting with extrapyramidal symptoms, psychosis, dementia, and retinal degeneration. This report presents a case exhibiting dystonia, retinitis pigmentosa, and psychotic symptoms, accompanied by classical magnetic resonance imaging (MRI) feature. MRI of brain of two asymptomatic siblings of index case also demonstrated the characteristic “eye of the tiger” sign.